Skewness and kurtosis properties of income distribution models - James B. McDonald; Jeff Sorensen; Patrick A. Turley (Luxembourg Income Study (LIS), 2011)
This paper explores the ability of some popular income distributions to model observed skewness and kurtosis. We present the generalized beta type 1 (GB1) and type 2 (GB2) distributions' skewness-kurtosis spaces and clarify and expand on previously known results on other distributions' skewness-kurtosis spaces. Data from the Luxembourg Income Study are used to estimate sample moments and explore the ability of the generalized gamma, Dagum, Singh-Maddala, beta of the first kind, beta of the second kind, GB1, and GB2 distributions to accommodate the skewness and kurtosis values. The GB2 has the flexibility to accurately describe the observed skewness and kurtosis.
Keywords: C16; C52; E25; 330; skewness; kurtosis; generalized beta type 2 distribution; generalized gamma distribution